KINERJA BADAN NARKOTIKA KABUPATEN DALAM PENANGGULANGAN PENYALAHGUNAAN NARKOBA DI KECAMATAN PANCA RIJANG KABUPATEN SIDENRENG RAPPANG - Rezky Putra Ramadhan Rezky Ramadhan (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2020)
The purpose of this study was to determine the performance of the District Narcotics Agency (BNK) in Drug Abuse Management in the Panca Rijang District of Sidenreng Rappang Regency and the factors that influenced the Performance of the Narcotics Agency (BNK) in drug abuse prevention in Panca Rijang Sub-District, Sidenreng Rappang District. The population is 26,149 people in Panca Rijang Subdistrict aged 18 years and above. The sample in this study was 100 people in the District of Panca Rijang, based on purposive sampling techniques or determination of samples with certain criteria with sampling techniques using Slovin formula.. This type of research is quantitative descriptive with basic research, survey research with descriptive explanatory level, and the type of data in this study is quantitative research.The results of the Performance of the District Narcotics Agency (BNK) in the prevention of drug abuse in the Panca Rijang District of Sidenreng Rappang Regency are in the